Deciphering the concurrence of comammox, partial denitrification and anammox in a single low-oxygen mainstream nitrogen removal reactor - Li, Xu (2023)
One-stage anammox-based autotrophic nitrogen removal technology has attracted increasing interest to sustainable biological nitrogen removal for future wastewater treatment. However, its application in mainstream municipal wastewater treatment is still challenging due to low nitrogen and high organics of raw wastewater. Herein, a novel Simultaneous Carbon Oxidation, partial Comammox, Denitratation and Anammox (SCOCDA) was firstly developed in a single sequencing batch biofilm reactor operated at a dissolved oxygen concentration of ∼0.5 mg/L for treating synthetic municipal wastewater (50 mg/L NH4+-N and 100-250 mg/L COD). The long-term operation showed that almost complete COD and nitrogen removal performance could be achieved at a carbon/nitrogen ratio (COD/NH4+-N) of 3-5 with the corresponding effluent total nitrogen (TN)＜5 mg/L. Microbial community and amoA-targeting amplicon sequencing analysis further verified that comammox Nitrospira spp., denitrifier Thauera and other aerobic/facultative heterotrophs could work synergistically with anammox bacteria, Candidatus Kuenenia. Moreover, nitrogen metabolic and inorganic carbon fixation pathways through the interaction between comammox and anammox were also revealed with the aid of Kyoto Encyclopedia of Genes and Genomes (KEGG). Lastly, potential application of proposed SCOCDA process was illustrated. This research sheds new light on advanced nitrogen removal towards limit of technology via the synergy of comammox and anammox.